An unusual trilogy: a case of comorbid aHUS, Fabry disease, and hypertrophic cardiomyopathy - Li, Qian; Yu, Lichun; Wang, Jing; Yang, Zhenle; Duan, Yanhua; Zhen, Junhui; Sun, Shuzhen (Frontiers in Medicine, 2026)
A 7-year-old boy was admitted to the hospital for abdominal pain, vomiting, and edema. Examinations revealed microvascular hemolytic anemia, thrombocytopenia, acute kidney injury, and hypocomplementemia. He was diagnosed with atypical hemolytic uremic syndrome (aHUS), and treatment was initiated with a methylprednisolone pulse, followed by cyclophosphamide, mycophenolate mofetil, and fresh frozen plasma infusion, leading to remission. At the age of 12, he developed numbness in his fingers and pain in his toes while being febrile. At the age of 17, he presented with aggravated toe pain, renal impairment (creatinine concentration of 156 μmol/L; eGFR of 38.4 mL/min/1.73 m2), and remarkable left ventricular hypertrophy accompanied by obstruction of the left ventricular outflow tract. Screening for Fabry disease (FD) revealed a decrease in alpha-galactosidase A (α-GalA) activity <1.00 μmol/L/h, along with the identification of a variant of the α-GalA gene: c.611G > A (p.Trp204Ter). His father had a history of hypertrophic cardiomyopathy (HCM). Therefore, whole-exome sequencing of the pedigree was performed, and the results revealed an additional likely pathogenic MYH7 variant (c.1063G > A) (p.Ala355Thr). The final diagnoses included FD (classic), aHUS, and HCM (Fabry disease and MYH7 variants). Despite undergoing enzyme replacement therapy for FD, the patient’s renal function progressed to chronic kidney disease (CKD) stage 5, and there was no improvement in cardiac hypertrophy after 2 years. This case highlights the diagnostic challenges and complex management of patients with multiple rare disorders and a compounded genetic background.